Possibilities of Cosmeticizing Financial Situations through Accounting Policies and Options – Theoretical and Applicative Particularities (Acta Universitatis Danubius. Œconomica, 2023)
The purpose of the research is to make a foray into the presentation and perception of accounting policies and options possible to be adopted by an economic entity, as well as to reveal their impact on the information provided by the financial statements. In this sense, a theoretical research of the specialized literature and the accounting legislation in force was undertaken, as well as an empirical research in which the comparative analysis method was used, the aim being to demonstrate the implications of the accounting policies chosen by the company on the quality of the financial - accounting information provided by the financial statements.